Reporting in the MENA region cyber engagement and pan-Arab social media - ʻĀyish, Muḥammad ʻIṣām; Mellor, Noha 1969- (Rowman & Litlefield, 2015)
In this examination of media practice in the Arab region, Ayish and Mellor examine how journalists are adjusting to the new realities of reporting in the digital age.